Why drivers use cell phones and support legislation to restrict this practice. (July 2016) - Sanbonmatsu, David M.; Strayer, David L.; Behrends, Arwen A.; Ward, Nathan; Watson, Jason M.
Highlights: Many drivers are hypocritical in using phones while supporting restrictions. Many people believe they can drive safely while using mobile devices. People lack confidence in others ability to drive safely while distracted. The threat to safety of others' usage of phones predicts support for restrictions. Abstract: The use of cell phones while driving is ubiquitous, particularly in countries where the practice is legal. However, surveys indicate that most drivers favor legislation to limit the use of mobile devices during the operation of a vehicle. A study was conducted to understand this inconsistency between what drivers do and what they advocate for others. Participants completed a survey about their driving attitudes, abilities, and behaviors. Following previous research, drivers reported using cell phones for benefits such as getting work done. The hypocrisy of using cell phones while advocating restrictions appears to stem from differences in the perceived safety risks of self vs. others' use of cell phones. Many if not most drivers believe they can drive safely while using mobile devices. However, they lack confidence in others' ability to drive safely while distracted and believe that others' use of cell phones is dangerous. The threat to public safety of others' usage of mobile devices was one of the strongest independent predictors of support for legislation to restrict cell phone use.